Isolation of Cryptococcus neoformans and other opportunistic fungi from pigeon droppings - Maryam Soltani; Mansour Bayat; Seyed J Hashemi; Mohammadali Zia; Nader Pestechian (Journal of Research in Medical Sciences, 2013)
Background: Invasive fungal infections cause considerable morbidity and mortality in immunocompromised hosts. Pigeon droppings could especially be a potential carrier in the spread of pathogenic yeasts and mold fungi into the environment. The objective of this study was to isolation of Cryptococcus neoformans and other opportunistic fungi from pigeon droppings. Materials and Methods: One hundred twenty samples of pigeon droppings were suspended 1:10 in saline solution and then cultured. Identification of C. neoformans was performed on bird seed agar, presence of a capsule on India ink preparation, urease production on urea agar medium and RapID yeast plus system. The identification of candida species was based on micro-morphological analysis on corn meal-Tween 80 agar, RapID yeast plus system and growth in CHROMagar candida. The identification of other fungi was based on macromorphologic, microscopic, biochemical and physiological characteristics. Results: The highest frequency of yeasts and mold fungi were observed in Candida albicans 6.6% and Penicillium spp. 25%. The frequency rate of C. neoformans isolation was 2.5%. Conclusion: Several types of fungi are present in pigeon droppings that can spread in environment and transmit to children and elderly as well as immunocompromised patients who are at increased risk of contracting opportunistic diseases.